Answer:
(5x + -4y)(3x + 7y) = 0
Multiply (5x + -4y) * (3x + 7y)
(5x * (3x + 7y) + -4y * (3x + 7y)) = 0
((3x * 5x + 7y * 5x) + -4y * (3x + 7y)) = 0
Reorder the terms:
((35xy + 15x2) + -4y * (3x + 7y)) = 0
((35xy + 15x2) + -4y * (3x + 7y)) = 0
(35xy + 15x2 + (3x * -4y + 7y * -4y)) = 0
(35xy + 15x2 + (-12xy + -28y2)) = 0
Reorder the terms:
(35xy + -12xy + 15x2 + -28y2) = 0
Combine like terms: 35xy + -12xy = 23xy
(23xy + 15x2 + -28y2) = 0
Solving
23xy + 15x2 + -28y2 = 0
Solving for variable 'x'.
Factor a trinomial.
(5x + -4y)(3x + 7y) = 0
Step-by-step explanation: